Development of online student worksheet based on scientific approach to improve critical thinking ability in Junior High School - Eris Wulan; Liska Berlian; Septi Kurniasih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
This research is based on learning activities in several junior high schools in Tangerang that have yet to be oriented to students' integration and critical thinking skills. The ability to think critically in learning can be done by growing it through electronic teaching materials like an electronic worksheet with a scientific approach. STUDENT WORKSHEET is compiled using a flip pdf builder application to support learning in the 21st century by utilizing technology. The purpose of this study was to design student worksheets in electronic form with a scientific approach to the theme of the role of biotechnology in food diversification to foster the critical thinking skills of class IX students. The research method used is Research and Development (R&D) development research with Thiagarajan development design through modifications that are tailored to the needs of researchers with being limited to the expert validation stage, which includes the following stages: Definition ( Define), Design ( Design ), Development ( Develop ). The instrument used is a material expert validation questionnaire sheet, media expert, and science teacher. The results of this study indicate the validity of the student worksheet by obtaining an average percentage value of 79.92% with a valid category which includes material experts at 63.7% with a valid category, teaching media experts at 81.96% with very valid categories, and teachers IPA is 94.11% with a very valid category.